The utility of real‐world evidence for benefit‐risk assessment, communication, and evaluation of pharmaceuticals: Case studies. Issue 12 (17th November 2020) - Radawski, Christine A.; Hammad, Tarek A.; Colilla, Susan; Coplan, Paul; Hornbuckle, Kenneth; Freeman, Emily; Smith, Meredith Y.; Sobel, Rachel E.; Bahri, Priya; Arias, Ariel E.; Bennett, Dimitri
Abstract: Purpose: In recent years, novel types of real‐world evidence (RWE) have played a role in various decision‐making processes relating to medicinal products, including regulatory approval, patient access, health technology assessment, safety monitoring, clinical use, and post‐approval lifecycle management. We therefore reviewed the potential utility of RWE in the cycle of medicinal product benefit‐risk (BR) assessment, communication/risk minimization and evaluation ("BRACE"). Methods: A convenience sample of illustrative studies was drawn from the published literature and examined. Specifically, we examined the purpose for using RWE, the type of RWE used, its novelty and how it might be integrated with other data and activities of the BRACE cycle, and how it contributed to regulatory decision‐making. Results: Eight studies were selected with each illustrating a different activity in the BRACE cycle ranging from BR assessment in the preapproval setting, post‐approval assessment of safety or effectiveness, communicating BR information to patients and healthcare professionals, and evaluating the effectiveness of risk minimization initiatives to support a positive BR balance. Conclusions: RWE has an important role in informing regulatory decision‐making regarding the BR management of medicines. With increasing digitalization, facilitating data collection and stakeholder engagement in health, this role is only expected to expand in the future. To reach the full potential of RWE, both regulators and sponsors will need to be familiar with a range of existing and emerging methods for generating and analyzing such evidence appropriately and achieve convergence regarding how different types of RWE can best be used to inform BR management and decision‐making.